Antigua and Barbuda. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Antigua and Barbuda during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as veterinary, livestock, safety, costs, production, agricultural development, risk management, good practices. manufacturing, agribusiness, insurance, natural disaster management, school gardens, and food preservation. Finally, work was done on combating greenhouse gasses, on the inclusion of youth, drying products in the sun, on the production of vegetables and fruits, such as mangoes, and on the control of diseases, such as avian influenza and bovine tuberculosis.